Research skills of student counselors in west Iran University of Medical Sciences (Kurdistan, Kermanshah, Hamadan, Ilam) in 2018 - Yousefi, Fayegh; Tairi, Fariba; Abbaspour, Parastoo; Panahi, Soheila; Davoodian, Zohreh (Majallah-i ravānshināsī va ravānʹpizishkī-i shinākht = Shenakht journal of psychology and psychiatry, 2021)
Introduction: Research is one of the effective factors in promoting counseling and psychotherapy services; therefore, it is necessary to assess the research skills of counselors. Aim: This study aimed to investigate the research skills of consultants of student counseling departments of Medical Universities in the Western Region of the country (Kurdistan, Kermanshah, Hamedan, Ilam, and Sanghor-Asadabad School of Nursing) in 2018. Method: In this descriptive study, 41 counselors of student counseling offices of Medical Universities in the Western Region of the country in 2018 were surveyed by census sampling method. The data collection tool was Marah (2010) Research Skills Assessment Questionnaire. Research data were analyzed by the Pearson correlation method in SPSS software version 22. Results: In the descriptive findings section, the results showed that 61% of the counselors were female and %39 were male, 63.4% of the respondents had a master's degree and 41% had a work experience of one to five years. The mean scores of methodological skills were measured as the optimal mean of 3.06±8.6 and the mean scores of statistical skills as the unfavorable means were measured as 2.06±5.2. Only the educational level of the subjects had a significant relationship with the level of research skills of the subjects (P<000). Conclusion: In general, it can be concluded that the level of research skills of consultants was moderate; the weakness of research perspective in some consultants and also giving priority to consulting services over research work in the field can be Factors for this issue.